Macrophage plasticity and function in cancer and pregnancy - Yin, Tingxuan; Li, Xinyi; Li, Yanhong; Zang, Xingxing; Liu, Lu; Du, Meirong (Frontiers in Immunology, 2024)
As the soil of life, the composition and shaping process of the immune microenvironment of the uterus is worth exploring. Macrophages, indispensable constituents of the innate immune system, are essential mediators of inflammation and tissue remodeling as well. Recent insights into the heterogeneity of macrophage subpopulations have renewed interest in their functional diversity in both physiological and pathological settings. Macrophages display remarkable plasticity and switch from one phenotype to another. Intrinsic plasticity enables tissue macrophages to perform a variety of functions in response to changing tissue contexts, such as cancer and pregnancy. The remarkable diversity and plasticity make macrophages, particularly intriguing cells given their dichotomous role in either attacking or protecting tumors and semi-allogeneic fetuses, which of both are characterized functionally by immunomodulation and neovascularization. Here we reviewed and compared novel perspectives on macrophage biology of these two settings, including origin, phenotype, differentiation, and essential roles in corresponding microenvironments, as informed by recent studies on the heterogeneity of macrophage identity and function, as well as their mechanisms that might offer opportunities for new therapeutic strategies on malignancy and pregnancy complications.